Efektivitas Penurunan Kadar Besi (Fe) pada Air Sumur dengan Filtrasi Serbuk Cangkang Kerang Variasi Diameter Serbuk - Intan Noer Auliah; Khambali Khambali; Ernita Sari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
Iron levels (Fe) in water that exceed the quality standard may cause physical changes in water and induce diseases in humans. One method of reducing iron content (Fe) is by using filtration with powdered seashells as adsorbent. The purpose of this study is to understand the decrease in iron content (Fe) in well water after filtration with powdered seashells 10 mesh, 40 mesh, and 100 mesh. This was an experimental study using Pretest-Posttest Control design. Data were analyzed with One Way ANOVA test. The average results of iron (Fe) before treatment with shell powder fillings of 10 mesh, 40 mesh and 100 mesh were 2.01 mg / L and the average concentration after treatment with shell powder filming of 10 mesh, 40 mesh and 100 mesh the result were 1.64 mg / L, 1.11 mg / L, and 0.49 mg / Lmost effective reduction iron content (Fe) occurred at treatment using filtration of shell powder of shell size 100 mesh that with an average equals to 75.37%. One Way ANOVA test showed resulted in p-value